Role of Water Resources in Determining Spatial Planning of Region - Anna, Alif Noor (Forum Geografi, 1998)
In planning a spatial order in a territory , it is necessary to take acount of three aspects of natural resources, human resources, and living environment. Based on the reality, so it is necessaryÂ to think of two sides: potential human resources and environment and human resources. One of the resources that is absolutely needed by creatures is water. Concerning the spatial order, the water is greatly needed in a variety of life. As the other resources, the reserve of the water also get limited. Because of its limitation, it is necessary to control the potential water sources in a territory before determining a design of good spatial order. It means that in planning the spatial order must be based on the rule and regulation of preserving its resource.